Assessing the ecological impacts of ageing on hazard potential of solid waste landfills: A green approach through vermitechnology. (1st November 2019) - Paul, Sarmistha; Choudhury, Moharana; Deb, Utsab; Pegu, Ratul; Das, Subhasish; Bhattacharya, Satya Sundar
Abstract: Information about the layer wise variation in Municipal Solid Waste (MSW) dumps, their environmental consequences, and leaching dynamics are rather scarce. MSW samples were, therefore, collected from three layers of a 30 year old dumping site at Silchar (India). Significant variations in pH, density, and metal toxicity were evidenced in different layers of the MSW pile. Physical characteristics (grain size, porosity etc) noticeably varied along the depth as substantiated by SEM analysis. FTIR analysis further revealed predominance of amines and alkenes in the deeper layers. NPK availability was found to be 1.5–2 folds lower in the deepest layer (L3) than the upper layers (L1 and L2). However, Pb, Cr, and Cd availability was significantly high in the middle layer (L2). Lab scale leaching experiments showed that metals (Fe, Cu, and Pb), phosphates and sulphates can greatly contaminate the soil and aquatic ecosystems in the long run. Visual MINTEQ model predicted possibilities of time dependent long range leaching of Fe, Cu, and Pb. Attributes like pollution index, ecological risk index, and geo-accumulation index also revealed adverse impacts of the deeper landfill layers on the surrounding environment. The potentially toxic MSWs were sanitized via vermitechnology by utilizing the bioaccumulation traits of earthworms ( Eisenia fetida ). On an average more than 3–5 fold reduction in overall environmental risk could be achieved in the vermicomposted and composted MSW fractions. The N, P, and K levels increased by 85%, 41%, and 68% in the vermicomposted MSW + Cow dung (1:1) feedstock. This also induced greater seed viability than composted mixtures. Finally, the economic evaluation of the treatment technologies was performed to realize their industrial value. Highlights: Metal pollution intensity of landfilled waste layers increased along their depth. NPK availability was 1.5–2 folds lower in the deepest layer than the top ones. Visual MINTEQ predicted rapid Pb, Fe, and Cu dissolution from aged waste layers. Pollution index and ecological risk sharply reduced in the vermi-treated waste. Vermicomposted MSW was economical and significantly induced seed germination.